The Application of the Question Students Have (QSH) Strategy to Enhance Students' Learning Results in Mathematics at Grade VI SDN 07 Tiumang. - Miyato Miyato (The Future of Education Journal, 2023)
Abstrak The condition of learning mathematics until now is still dominated by the teacher as a provider of knowledge so that students get more information from the teacher's explanations alone, as a result the students' thinking is less developed. The impact of this learning is that the results of learning mathematics are not optimal. Question Students Have is a strategy to encourage students to have the courage to ask questions in written form. The purpose of this study was to determine student learning outcomes taught using the Question Students Have strategy in Class VI students at SDN 07 Tiumang. The type of research used in this research is experimental research, namely Pre-Experimental with the One Group Pre-test and Post-test research design. The sample of this research was 23 Class VI students at SDN 07 Tiumang, Dharmasraya Regency. The research instruments used in this study were student learning outcomes tests, documentation and observation sheets. The data analysis technique used is descriptive statistical analysis with PTK cycles. The results showed an increase in student learning outcomes in mathematics seen from the class average score. The value before the intervention was 39.78%. The value in cycle I increased to 67.82% and there was another increase in cycle II to 82.40%. Based on these results it was concluded that the Question Students Have strategy can improve the learning outcomes of mathematics in class VI students at SDN 07 Tiumang.